Membangun Soft Skill Siswa SMK Bintang Nusantara Melalui Pelatihan Optimalisasi Pengelolaan Live Shopee Untuk Konten Pemasaran - Okta Irawati; Sutrisno; Iis Istiqomah (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The government pays attention to vocational education, including vocational high schools (SMK). The aim of the various programs that have been launched by the government is to produce graduates who are able to meet industry needs. Bintang Nusantara Vocational School offers skills competency education such as AKL, OTKP, ​​Multimedia with graduates ready to work, become entrepreneurs or continue their education. To achieve this, the education and learning process must refer to and comply with the applicable curriculum in accordance with the school's vision, mission and goals. Subjects that discuss Digital Marketing teach how to market via the internet. This marketing can be done through web pages or using the social media provided. By doing business online, of course it will be easier and will not require a lot of costs, to rent a shophouse, buy stock, pay employees and so on. Carrying out online buying and selling activities requires special skills to achieve success. So we are hereby proposing this PkM activity with the theme of building Soft Skills for Bintang Nusantara Vocational School students through training in optimizing live shopee management for marketing content. The presentation by the resource person and then continuing to practice the features available on Shopee live streaming is expected to increase knowledge regarding online selling skills in a good and structured manner.